Pengaruh Kepemimpinan Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Pos Indonesia (Persero) Cabang Ciputat Tangerang Selatan - Lenni Ridawati Tampubolon; Ali Zaenal Abidin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study is to determine the effect of leadership and the physical work environment on employee performance at PT Pos Indonesia (Persero), Ciputat Branch, South Tangerang. This study uses a quantitative research method. The sampling technique was determined using the Slovin formula, resulting in a total of 114 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing.The results of the study indicate that leadership has a significant effect on employee performance, with a coefficient of determination of 55.6%, and the hypothesis test shows that the calculated t-value is greater than the t-table value (6.857 > 1.981). The physical work environment also has a significant effect on employee performance, with a coefficient of determination of 69.6%, and the hypothesis test shows that the calculated t-value is greater than the t-table value (6.240 > 1.981). Furthermore, leadership and the physical work environment simultaneously have a significant effect on employee performance, as indicated by the regression equation Y = 47.686 + 0.509X1 + 0.492X2. The coefficient of determination is 70.5%, while the remaining 29.5% is influenced by other factors. The hypothesis test shows that the calculated F-value is greater than the F-table value (36.354 > 3.080).